(untitled) (International Journal of Current Engineering and Technology, 2015)
In the context of depletion of fossil fuels, ever increase of pollution levels with fossil fuels, search for alternative fuels has become pertinent. Vegetable oils are important substitutes for diesel fuel as their properties are comparable to diesel fuel. Investigations were carried out to study exhaust emission of diesel engine with air gap insulated low heat rejection (LHR–3) combustion chamber consisting of air gap insulated piston with 3 mm air gap, with superni (an alloy of nickel) crown, air gap insulated liner with superni insert and ceramic coated cylinder head with crude vegetable oil with varied injector opening pressure. Exhaust emissions [ particulate emissions and nitrogen oxide levels] were determined at various values of brake mean effective pressure (BMEP) of the LHR–3 combustion chamber and compared with neat diesel operation on conventional engine (CE) and vegetable oil operation at similar operating conditions. Engine with LHR–3 combustion chamber with vegetable oil operation showed reduction of particulate emissions at manufacturer’s recommended injection timing of 27o bTDC, and these emissions decreased marginally with increased injector opening pressure n comparison with CE with diesel and vegetable oil at 27obTDC. However, LHR-3 engine drastically increased nitrogen oxide levels in comparison with conventional engine with vegetable oil.